Biotransformation of Furaltadone, Furazolidone and Nitrofurazone using Aspergillus Tamarii isolate TN-7 : in Vitro Residual Identification and Quantification by HPLC-DAD - S Mohammad, N; I A Halim, M; M Mahat, M; F Safian, M; Z Ariffin, Z (International Journal of Engineering and Technology, 2019)
Nitrofurans (NFs) such as furaltadone (FTD), furazolidone (FZD) and nitrofurazone (NFZ) have been used as antibacterials and growth promoters for the poultry and aquaculture industry. These antibiotics have now been banned from use due to their carcinogenic properties; therefore there is an urgent need to remove or degrade NFs from contaminated areas. Aspergillus tamarii isolate TN-7 isolated from antibiotic overexposed soil shows an ability to degrade the NFs antibiotics. After 5 days of incubating of Aspergillus tamarii isolate TN-7 with 500 µg/mL NF, the residual of the NF concentration was determined by High-Performance Liquid Chromatography-diode array detector (HPLC-DAD). Solid phase extraction was performed to clean-up the fermentation broth prior to HPLC-DAD analysis.  Antimicrobial of the NFs residues showed a decreased in the percentage of inhibition that FTD, FZD and NFZ were reduced to to 85.71 %, 75.86 % and 70.97 % after 96 hours of incubation. Quantification using HPLC-DAD showed, after 96 hours of incubation, Aspergillus tamarii isolate TN-7 reduced furaltadone, furazolidone and nitrofurazone to 86.73 %, 37.49 % and 29.17 % respectively. This finding shows that Aspergillus tamarii isolate TN-7 has the potential to be used as a bioremediation tool in removing NF antibiotics from the contaminated areas.